Coordinated regulation of BACH1 and mitochondrial metabolism through tumor-targeted self-assembled nanoparticles for effective triple negative breast cancer combination therapy - Xuan Yang; Yalong Wang; Junke Zhao; Hehui Rong; Yujun Chen; Mengting Xiong; Xiaoxing Ye; Shihui Yu; Haiyan Hu (Elsevier, 2022)
The poor prognosis of triple negative breast cancer (TNBC) results from a lack of approved targeted therapies coupled with aggressive proliferation and metastasis, which is associated with high recurrence and short overall survival. Here we developed a strategy by employing tumor-targeted self-assembled nanoparticles to coordinately regulate BACH1 (BTB domain and CNC homology 1) and mitochondrial metabolism. The BACH1 inhibitor hemin and mitochondria function inhibitor berberine derivative (BD) were used to prepare nanoparticles (BH NPs) followed by the modification of chondroitin sulfate (CS) on the surface of BH NPs to achieve tumor targeting (CS/BH NPs). CS/BH NPs were found to be able to inhibit tumor migration and invasion by significantly decreasing the amounts of tumor cell metabolites, glycolysis and metastasis-associated proteins, which were related to the inhibition of BACH1 function. Meanwhile, decreased mitochondrial membrane potential, activated caspase 3/9 and increased ROS production demonstrated coordinated regulation of BACH1 and mitochondrial metabolism. In a xenograft mice model of breast cancer, CS/BH NPs significantly inhibited tumor growth and metastasis due to the synergetic effect of hemin and BD without showing obvious toxicities for major organs. In sum, the results of efficacy and safety experiments suggest potential clinical significance of the prepared self-assembled CS/BH nanoparticles for the treatment of TNBC.